2022
DOI: 10.1088/1755-1315/1071/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Integrated mapping of the earthquake-induced liquefaction in Wates Groundwater Basin, Kulon Progo for land use planning consideration: A preliminary study

Abstract: Since the development of New Yogyakarta International Airport (NYIA), land use planning and development in Wates Groundwater Basin, Kulon Progo, Indonesia, becoming more crucial. A regional-scaled study led by Buana et al. (2019) pointed out the area as moderate-high susceptibility to liquefaction. This study provides updated land-use conditions and a detailed liquefaction susceptibility map using Geographic Information System and Multi-Criteria Analysis (GIS-MCA) from the previous research data by Maulana (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The final map that resulted from this method is showing a significantly different zonation from the previous result from [9]. In the final map of this research, the high susceptibility area is distributed also in the south and east parts, while in the previous research, only high susceptibility showed in the same part.…”
Section: Comparison With the Previous Studycontrasting
confidence: 65%
See 2 more Smart Citations
“…The final map that resulted from this method is showing a significantly different zonation from the previous result from [9]. In the final map of this research, the high susceptibility area is distributed also in the south and east parts, while in the previous research, only high susceptibility showed in the same part.…”
Section: Comparison With the Previous Studycontrasting
confidence: 65%
“…The combined method has produced slightly different zones of liquefaction susceptibility if compared to the result from [9], which only applies the AHP method. It indicates that the combined method has reduced the subjectivity in the parameters and produced a more detailed map even with the same data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research area is situated within the discharge area of the Wates groundwater basin, where water flows from the north to the south and east. The study area is assessed to have a high potential for liquefaction due to its shallow groundwater, thick sandy sediments, and high seismic activity [20].…”
Section: Fig5 Groundwater Depth (Clear Weather No Rain)mentioning
confidence: 99%